2017
DOI: 10.1021/acs.nanolett.7b03314
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Magnetic Hybridization of a Spinterface through Insertion of a Two-Dimensional Magnetic Oxide Layer

Abstract: Interfaces between organic semiconductors and ferromagnetic metals offer intriguing opportunities in the rapidly developing field of organic spintronics. Understanding and controlling the spin-polarized electronic states at the interface is the key toward a reliable exploitation of this kind of systems. Here we propose an approach consisting in the insertion of a two-dimensional magnetic oxide layer at the interface with the aim of both increasing the reproducibility of the interface preparation and offering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Notably, the net magnetization of the Cr atoms in the oxide layer is always opposite to the underlying Fe one, as in absence of molecules, confirming the antiferromagnetic coupling between the overlayer and the substrate evidenced by the experiments [14]. Indeed, also in the configurations The magnetic moment of the C atoms is three orders of magnitude smaller than that of the Cr atoms and its sign depends on the adsorption configuration.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Notably, the net magnetization of the Cr atoms in the oxide layer is always opposite to the underlying Fe one, as in absence of molecules, confirming the antiferromagnetic coupling between the overlayer and the substrate evidenced by the experiments [14]. Indeed, also in the configurations The magnetic moment of the C atoms is three orders of magnitude smaller than that of the Cr atoms and its sign depends on the adsorption configuration.…”
Section: Resultssupporting
confidence: 68%
“…In recent works [14][15][16] some of us focused on the C 60 /Fe(001) interface, both on the experimental and theoretical viewpoint. We demonstrated that the induced magnetic properties on the molecules depend on the spin polarization of the substrate states interacting with the molecule itself and by their decay toward vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] We identify in the passivation of the surface a viable strategy for tuning the molecular coupling. 25,26 Some earlier attempts are acknowledged, where ultrathin oxides [27][28][29] or graphene [30][31][32] were specifically used to change the nature of the interaction between the molecules and the substrate to indirect superexchange mediated by the interlayer. For most of these systems, however, scarce structural information about the molecular layers is reported.…”
mentioning
confidence: 99%
“…Selected PES spectra related to 1 molecular layer of C 60 on Fe(001), Fe(001)-p(1 Â 1)O, and Cr 4 O 5 =Fe have already been discussed in previous publications. 8,12 In Fig. 2, we present a set of normal emission PES spectra related to the C 60 =Cr 4 O 5 =Fe system, by reporting them as a function of molecular coverage.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…We have furthermore studied the magnetic hybridization at such interfaces and at the interface between a C 60 and a Cr 4 O 5 monolayer stabilized onto the Fe(001) surface. 12 Those investigations lead to the observation of spin-polarized fullerene states in all cases.…”
Section: Introductionmentioning
confidence: 98%